TATACARA PELAKSANAAN SHALAT BERJAMA’AH BERDASARKAN HADIS NABI - Syekh, A. Karim (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2018)
This "Procedure for Prayer of Prayer" was brought about by the fact that there were various phenomena and irregularities of the members of the prayer and some of the members who preceded their prayer movements instead of the priestly prayer movement, while all of them were in the position of following the priest as they were performing prayer in the congregation. Another phenomenon that can be seen is the range of movement of the prayer from one pillar to prayer to the next. For example, some raise both hands before saying takbiratulihram, others raise both hands in conjunction with the takbiratul ihram pronunciation and some raise both hands after the pronunciation of takbiratul ihram. With the emergence of a variety of prayer-worship practices like this if all congregations were able to understand it as al-Tanawwu 'fi al-'Ibadah there would be a sense of mutual tolerance among the congregation. However, if they are narrow-minded they will cause a breakdown in Islamic fellowship because they claim that they are right and accuse the other of being wrong, and some even consider the other person to be the culprit, misguided and misleading. To correct misunderstandings in some societies, the writing of the article: "Procedures for Prayer Prayers", based on the Sunnah of the Messenger of Allah and the explanations of the scholars / fuqaha 'is very important to be created and published to the public. It is hoped that this simple piece of writing will serve as a guide for readers in performing the prayer of the congregation.